PENINGKATAN MOTIVASI DAN KETERAMPILAN MENULIS TEKS EKSPLANASI KOMPLEKS MELALUI METODE KOOPERATIF PADA SISWA KELAS XI TSM 1 SMK NEGERI 2 MERANGIN - Drs. Zakaria (Fokus | Jurnal Pendidikan STKIP YPM Bangko, 2022)
This study aims to increase learning motivation and text writing skills complex explanation in class XI TSM 1 SMKN 2 Merangin by applying the picture and picture type cooperative method. This research is a classroom action research (CAR) which was carried out in two cycles. Each cycle consists of planning, implementing actions, observing, and reflecting. The research subjects were students of class XI TSM 1 SMKN 2 Merangin, totaling 33 students. Sources of data in this study are informants and documents. Data collection techniques used are observation, interviews, tests, and documentation. The validity of the data using data triangulation techniques, method triangulation, and review of informants. Data analysis used comparative descriptive analysis technique. The research procedure is an interrelated spiral model. The results showed that the application of the picture and picture cooperative method can improve motivation and writing skills of complex explanatory texts in class XI TSM 1 SMKN 2 Merangin from pre-action to cycle I and from cycle I to cycle II. This is indicated by an increase in: (1) student motivation from cycle I to cycle II which is quite significant; (2) the average score of students' writing skills, from 49.09 in the pre-action to 72.07 in the first cycle, and 82.07 in the second cycle.